Yield of roselle varieties in relation to apical pruning dates - Coria Ávalos, Víctor Manuel; Muñoz Flores, Hipólito Jesús; Toledo Aguilar, Rocío; Sáenz Reyes, J. Trinidad; Peñaloza Santa Cruz, Gabino; Barrera Ramírez, Rubén (Revista Mexicana de Ciencias Agrícolas, 2022)
The state of Michoacán is the second producer of roselle in Mexico. In this species, pruning helps to increase the yield of calyxes per unit area. Therefore, the objective was to evaluate the effect of apical pruning dates on the yield of four roselle varieties sown in the dry tropics of Michoacán. The study was conducted during the spring-summer cycle, 2021, in the locality of Melchor Ocampo, Cunuato, Churumuco, Michoacán. The varieties evaluated were: Reina Roja (control), Patriota, Estrella Costeña and Mulata. The apical pruning was carried out at 70, 90 and 107 days after sowing (das) and a control without pruning. A completely randomized experimental design with 4 x 4 factorial arrangement, with 10 repetitions, was used. The following variables were recorded: plant height, diameter at the base of the stem, number of lateral branches, fresh and dry weight of the calyxes per plant. An analysis of variance (ɑ= 0.05) was performed to determine the effect of the factors and their interactions, a mean comparison test (Tukey p≤ 0.05) and Pearson correlation between the variables were also performed. Apical pruning influenced the yield of calyxes of the four roselle varieties; the highest production was generated at 90 das; the Mulata and Estrella Costeña varieties produced 1 159.6 and 1 107.3 kg ha-1. The yields obtained in the trial exceeded those reported at the state (570 kg ha-1) and national (430 kg ha-1) levels. In general, roselle varieties responded positively to the apical pruning apical and if it is not carried out, the production decreases.